Pengaruh Perceived Ease of Use dan Perceived Risk Terhadap Customer Loyalty Melalui Customer Satisfaction pada Aplikasi E-Wallet - Julius Adi Wiratama; Munawaroh Munawaroh; Ringga Sentagi Asa (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The increasing use of digital wallet (e-wallet) services in Indonesia highlights the need for a deeper understanding of the factors that influence user loyalty. This research is conducted to examine the influence of perceived ease of use and perceived risk on customer loyalty, with customer satisfaction positioned as a mediating variable within the context of the LinkAja e-wallet application. A quantitative research design is employed by distributing structured questionnaires to 190 active LinkAja users across Indonesia. The collected data are analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 4.0. The findings indicate that perceived ease of use exerts a positive and statistically significant impact on customer satisfaction, whereas perceived risk demonstrates a negative and significant effect on customer satisfaction. In addition, customer satisfaction is found to positively influence customer loyalty and to significantly mediate the relationship between perceived ease of use and perceived risk on customer loyalty. These results imply that optimizing system usability and effectively managing perceived risks are crucial in improving user satisfaction and fostering long-term loyalty toward e-wallet services.